PENGARUH PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWERDISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATISSISWA KELAS VIII SMPN 1 BAYANG KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2013/2014 - Oktarini, Shinta; Zuzano, Fazri; Yunita, Alfi (Pendidikan Matematika, 2014)
ABSTRACTThis research was background by student understanding of mathematical concept still lower. This matter seen at result learn class student mathematics of VIII SMPN 1 Bayang School Year 2013 / 2014.This type of this  research is experiment. Research with random sampling techniques. Population in this research is all class student of VIII SMPN 1 Bayang school year 2013 /2014.The selected class of sampel is VIII1 as experiment class and of VIII5 as control class. Instrument used in this research is the tes of understanding of mathematical concept. Form of tes the used is form of esai with reliabilitas test is r11=0,93. Technique analyse data  used in this test is t.According to result of data analysis known that both class of sampel have normal distribution and is homogeneous at real level = 0,05. Result of hypothesis test obtained by t =2,36and ttable=1,68 hence hypothesis at this research is accepted. So that can be concluded that student  understanding of mathematical concept by applying study withactive learning type GQGA accompanied by quiz better than student understanding of mathematical concept with conventional study in class of VIII SMPN 1 Bayang.